PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI MELALUI MODEL JOYFUL LEARNING (Journal of Innovative Science Education, 2014)
AbstrakProses pembelajaran biologi menggunakan metode ceramah yang monoton dan penggunaan media charta merupakan penyebab suasana belajar yang membosankan dan tidak menarik. Penerapan media pembelajaran berbasis TIK melalui model joyful  learning  dibutuhkan  untuk  mengatasi  masalah  tersebut.  Penelitian  ini bertujuan untuk mengidentifikasi media yang dibutuhkan siswa, menghasilkan media, mengevaluasi kevalidan, keefektifan, dan kepraktisan media pembelajaran biologi berbasis TIK melalui model joyful learning. Jenis penelitian yang digunakan yaitu penelitian dan pengembangan. Desain penelitian menggunakan metode quasi experimental design dengan nonequivalent control group design. Dua kelompok siswa  tidak  dipilih  secara  random  tetapi  langsung  ditentukan  yaitu  kelas  XI IPA 1 sebagai kelas eksperimen dan kelas XI IPA 4 sebagai kelas kontrol. Hasil menunjukan bahwa media pembelajaran biologi berbasis TIK melalui model joyful learning sangat dibutuhkan siswa, memiliki karakteristik konten yang beragam, dinyatakan valid, efektif, dan memiliki kriteria nilai kepraktisan yang sangat tinggi.AbstractMonotonous method of  lecture and the usage of  charts as the teaching media in learning process of  biology is the cause of  boring and uninteresting atmosphere in learning process. The application of ICT-based biology teaching media through joyful learning model is needed to solve the issue. The aims of this study are to identify, to produce, to evaluate the validity, the effectiveness, and the practicality of  ICT–based biology teaching media through joyful learning model. This research is research and development. The design of the study is quasi experimental design with nonequivalent control group design. Group of experiment and group of control were not chosen at random, but they were directly determined by class XI Science 1 as the experimental class and class XI Science 4 as the control class. The results showed that ICT-based biology teaching media through joyful learning model is the most necessary for students. The media has the characteristics of various content, valid, effective, and has criteria of highly value practicality. Monotonous method of lecture and the usage of charts as the teaching media in learning process of biology is the cause of boring and uninteresting atmosphere in learning process. The application of ICT-based biology teaching media through joyful learning model is needed to solve the issue. The aims of this study are to identify, to produce, to evaluate the validity, the effectiveness, and the practicality of ICT–based biology teaching media through joyful learning model. This research is research and development. The design of the study is quasi experimental design with nonequivalent control group design. Group of experiment and group of control were not chosen at random, but they were directly determined by class XI Science 1 as the experimental class and class XI Science 4 as the control class. The results showed that ICT-based biology teaching media through joyful learning model is the most necessary for students. The media has the characteristics of various content, valid, effective, and has criteria of highly value practicality.